O criptojudaísmo dos cristãos-novos. Uma resistência de cinco séculos - Barrocas, Ricardo Lincoln Laranjeira (1990)
The author tries to approach the persistence of the cryptojudaic identity among the New Christians (converterd by constraint) by analysing the psychologic, social and historical data on this phenomenon. He also tries, upon a freudian view on religion, to explain Cryptojudaism as a resistance in the structure of wish in the Religion of the father opposed to the one in the Religion of the Son (Christianism). The autor also follows Jacques Lacan's theory on the logics of substitution of "significants" and the constitution of the Name-of-the-Father ali over this paper. He also explains the activities of the Inquisition as a trial to cease Cryptojudaism both as a social (political and economic) and religious phenomenon.